Adding unmanned aerial vehicles to HIV supply chains in remote settings: modeling feasibility and cost in Turkana, Kenya - Caleb Parker; Emily Evens; Kayla Stankevitz; Margaret Eichleay; Rick Homan; Michael Loogos; David Onyango (Journal of Global Health Reports)
# Background